2019
DOI: 10.1002/cam4.2369
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of dynamic contrast‐enhanced perfusion MRI in stratifying gliomas: A systematic review and meta‐analysis

Abstract: Background T1‐weighted dynamic contrast‐enhanced (DCE) perfusion magnetic resonance imaging (MRI) has been broadly utilized in the evaluation of brain tumors. We aimed at assessing the diagnostic accuracy of DCE‐MRI in discriminating between low‐grade gliomas (LGGs) and high‐grade gliomas (HGGs), between tumor recurrence and treatment‐related changes, and between primary central nervous system lymphomas (PCNSLs) and HGGs. Methods We performed this study based on the Preferred Reporting Items for Systematic Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 53 publications
(159 reference statements)
1
16
0
Order By: Relevance
“…Okuchi et al meta-analyzed nine studies for a total of 179 TR and 119 treatment-related changes. They found there to be a pooled sensitivity and specificity of 0.88 and 0.86, respectively, and an AUC of 0.89 [ 108 ]. ASL has been less investigated.…”
Section: Clinical Applications Of Hemodynamic Imaging In Gliomas—partmentioning
confidence: 99%
“…Okuchi et al meta-analyzed nine studies for a total of 179 TR and 119 treatment-related changes. They found there to be a pooled sensitivity and specificity of 0.88 and 0.86, respectively, and an AUC of 0.89 [ 108 ]. ASL has been less investigated.…”
Section: Clinical Applications Of Hemodynamic Imaging In Gliomas—partmentioning
confidence: 99%
“…Supplementary Table S2 shows studies of diagnostic accuracy for differentiating disease progression related and treatment-related effects. Two partially overlapping meta-analyses ( 56 , 88 ) calculated pooled sensitivity and specificity of 88–89% and 85–86%, respectively, based in combination on a total of 10 studies published from 2011 to 2015 including 371 patients. It is noteworthy that the diagnostic accuracy was higher in studies with model independent analysis ( 88 ) than in studies with two- or three-parameter models, while most recent studies (and clinical practice) typically employ three-parameter models.…”
Section: Resultsmentioning
confidence: 99%
“…The QIBA claim for K trans in the brain is that a longitudinal change of 21.3% of more can be attributed to true change rather than measurement error, noting that this is based on very limited literature 70,71 . This can also been seen from table 2, where only few DCE studies were identified in various meta-analyses, not allowing for reliable quantitative analyses and/or determination of thresholds 72 .…”
Section: Other Pmri Metrics As Imaging Biomarkersmentioning
confidence: 99%